The grand design - Hawking, Stephen (Bantam Books, 2010)
Along with Caltech physicist Mlodinow (The Drunkard's Walk), University of Cambridge cosmologist Hawking (A Brief History of Time) deftly mixes cutting-edge physics to answer three key questions-- Why is there something rather than nothing? Why do we exist? Why this particular set of laws and not some other?-- and explains that scientists are approaching what is called "M-theory," a collection of overlapping theories (including string theory) that fill in many (but not all) the blank spots in quantum physics. This collection is known as the "Grand Unified Field Theories."